Inovasi Sekolah Filial sebagai Solusi Inklusif Pendidikan dan Penguatan Kinerja Organisasi Pemerintah Daerah - Febriyanti; Bachtari Alam Hidayat; Rika Destiny Sinaga (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2026)
The Palembang City Government strives to improve access to education for all members of society by adopting various innovations, one of which is the implementation of filial schools. To support the operations of filial schools, the Palembang City Government allocates resources including teaching staff, facilities and infrastructure, as well as funding sourced from the regional budget and support from various stakeholders. In addition, coordination with social institutions and local communities also plays a role in ensuring the sustainability of this program. The objective of this study is to analyze the combined effect of filial school innovation and infrastructure support on the organizational performance of the Palembang City Government. This study uses a quantitative research design. The independent variables are filial school innovation (X1) and infrastructure support (X2), while the dependent variable is organizational performance (Y). Data were collected through questionnaires distributed to 100 respondents from various groups, including filial school students, parents, school principals, teachers, administrative staff, and representatives from the Education Office, Social Services Office, and Bappeda Litbang of Palembang City. The questionnaire consisted of 34 statements representing three research variables. The data were analyzed using multiple linear regression. The results of this study show that both filial school innovation and infrastructure support have a positive influence— both individually and jointly—on the organizational performance of the Palembang City Government. The government can enhance filial school innovation through curriculum development, teacher training, use of technology, and collaboration with parent schools and the community. In addition, the provision of supporting infrastructure and facilities for filial schools needs to be continuously improved.